Method for improving efficiency of perovskite solar cell

By introducing an insulating spacer layer into a perovskite solar cell and controlling its thickness by using electron beam evaporation method, the problem of interface recombination in the HTL-free structure is solved, the efficiency and stability of the battery are improved, and its service life is extended.

CN119546034AInactive Publication Date: 2025-02-28SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411565392.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing perovskite solar cells (PSCs), the interface composite phenomenon of the HTL-free structure limits the efficiency and stability of the battery, and the thickness of the insulating spacer layer is difficult to accurately control, affecting charge transfer and device life.

Method used

By introducing SiO2, Al2O3, MgO or BeO insulating spacer layers between the electron transport layer and the perovskite layer of a perovskite solar cell, and the thickness of the insulating spacer layer is accurately controlled by electron beam evaporation method, optimizing interface contact and charge transport paths.

Benefits of technology

It effectively reduces the interface recombination between the perovskite layer and the electron transport layer, improves the charge extraction efficiency and photoelectric conversion efficiency, extends the service life of the battery, and reduces production costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546034A_ABST
    Figure CN119546034A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the efficiency of a perovskite solar cell, and belongs to the technical field of solar cells. The insulating spacer film prepared between the electron transport layer and the perovskite layer of the perovskite solar cell by adopting the electron beam evaporation method has high uniformity, the cell interface structure can be optimized, defects are reduced, charge recombination loss is reduced, and the photoelectric conversion efficiency and stability are effectively improved. The insulating spacer layer not only can block external moisture and pollutants, reduce direct contact between the perovskite layer and the electron transport layer and prolong the service life of the cell, but also can inhibit internal ion migration and slow down performance degradation. By accurately regulating and controlling the thickness of the insulating spacer layer, charge transmission optimization and compound loss minimization are realized. An innovative technical path is provided for research and development of efficient and stable perovskite solar cells, and further development of the solar cell technology is expected to be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to a method for improving the efficiency of perovskite solar cells. Background Art

[0002] Perovskite solar cells (PSCs) have attracted much attention in recent years due to their excellent photoelectric conversion capabilities, adjustable band gaps, and low preparation costs. In order to further improve their efficiency and stability, researchers continue to explore methods to optimize device structures and materials, among which hole transport layer-free (HTL-free) perovskite solar cells have become a hot topic of research. Traditional PSCs generally contain a hole transport layer (HTL), but the introduction of HTL may not only lead to interface recombination, thereby reducing the photoelectric conversion efficiency, but also increase the complexity of the preparation process.

[0003] HTL-free perovskite solar cells have successfully achieved a photoelectric conversion efficiency of more than 20% by simplifying the structure and reducing interface recombination, and maintained an initial efficiency of more than 90% under long-term continuous irradiation. However, the interface recombination phenomenon in the HTL-free structure still exists, which restricts the overall efficiency and stability of the battery. To solve this problem, the researchers introduced an insulating spacer layer between the perovskite layer and the electron transport layer (ETL) to reduce the recombination of electrons and holes and optimize the charge transfer path, thereby further improving battery performance.

[0004] The thickness of the insulating spacer is a key factor affecting its function. An insulating layer that is too thick will hinder the effective transfer of charges, resulting in increased resistance and reduced efficiency; while an insulating layer that is too thin will not be able to fully suppress carrier recombination, affecting the photoelectric conversion efficiency. Therefore, a reasonable choice of the thickness of the insulating spacer is crucial to improving the performance of PSCs.

[0005] In addition, an insulating spacer layer of appropriate thickness can effectively block the penetration of moisture and impurities and protect the perovskite layer from environmental influences. This can not only maintain the efficient operation of the battery under long-term continuous irradiation, but also extend the actual service life of the device. At the same time, the thickness of the insulating layer is also critical to inhibiting ion migration and reducing interface defect recombination, thereby further improving the stability of the battery.

[0006] In terms of the manufacturing process, precise control of the thickness of the insulating spacer layer is the key to ensuring its functionality and stability. Different deposition methods, such as spin coating, knife coating, and chemical vapor deposition, will affect the uniformity of the final thickness. Therefore, the selection of thickness is also an important part of the optimization of the manufacturing process.

[0007] At present, commonly used insulating barrier layer materials include fullerenes, organic polymers (such as PMMA), and metal oxides (such as TiO2, ZrO2). These materials have improved the stability and efficiency of the device to a certain extent, but there is still room for further improvement in the long-term protection of the perovskite layer and the charge transfer efficiency. Therefore, how to reasonably select the thickness of the insulating spacer layer to achieve optimal charge transfer and minimize recombination losses is a technical challenge that needs to be solved urgently. Summary of the invention

[0008] The present invention aims to solve the problems and defects in the above-mentioned prior art. The present invention provides a method for improving the efficiency of perovskite solar cells and its application, which achieves optimal charge transfer and minimum recombination loss by precisely controlling the thickness of the insulating spacer layer, and provides a new technical approach for the research and development of efficient and stable perovskite solar cells.

[0009] In a first aspect, the present invention provides a method for improving the efficiency of a perovskite solar cell, wherein an insulating spacer layer is introduced between an electron transport layer and a perovskite layer of the perovskite solar cell;

[0010] The thickness of the insulating spacer layer is 0.1 nm to 1 μm.

[0011] Furthermore, the insulating spacer layer of the present invention is SiO2, Al2O3, MgO, BeO;

[0012] The insulating spacer layer is prepared by electron beam evaporation.

[0013] The SiO2, Al2O3, MgO, and BeO insulating spacer layers provided by the present invention effectively reduce the interface recombination between the perovskite layer and the electron transport layer, reduce energy loss, improve charge extraction efficiency, and provide an excellent barrier to block the erosion of the perovskite layer by moisture and environmental factors, thereby extending the service life of the battery.

[0014] In a second aspect, the present invention provides a method for preparing a perovskite solar cell, comprising: depositing and annealing an electron transport layer and an insulating spacer layer on an anode substrate by electron beam evaporation; preparing a perovskite layer and a hole transport layer by solution spin coating, and annealing the perovskite layer; and preparing a cathode by thermal evaporation.

[0015] Furthermore, the FTO conductive glass of the anode substrate of the present invention is ultrasonically cleaned with deionized water, acetone, isopropyl ketone and anhydrous ethanol in sequence, and then blown dry with nitrogen.

[0016] Furthermore, the parameters of the electron beam evaporation method of the present invention are set as follows: the vacuum degree is 1×10 -5 ~5×10 -3 Pa, temperature is 100-350°C, deposition rate is 0.1-1A / s, oxygen flow rate is 5-20sccm;

[0017] The conditions for annealing the electron transport layer and the insulating spacer layer are: annealing temperature is 300-800° C., and annealing time is 1-3 hours.

[0018] Furthermore, the spin coating process of the perovskite layer of the present invention is 500-1500 rpm for 10 seconds, and then 3000-6000 rpm for 30 seconds;

[0019] The conditions for annealing the perovskite layer are: annealing temperature is 190-210° C., and annealing time is 5-15 min.

[0020] Furthermore, the spin coating process of the hole transport layer of the present invention is 5000-7000 rpm for 30 seconds.

[0021] Furthermore, the rate of the thermal evaporation method of the present invention is 1 to 3 A / s.

[0022] In a third aspect, the present invention provides a perovskite solar cell produced by the above method.

[0023] Furthermore, the perovskite solar cell of the present invention comprises an electron transport layer, an insulating spacer layer, a perovskite layer, a hole transport layer and a cathode which are sequentially arranged on an anode substrate.

[0024] Furthermore, the anode substrate of the present invention is FTO conductive glass;

[0025] The electron transport layer is TiO2;

[0026] The perovskite layer is CsPbI3-xBrx;

[0027] The hole transport layer is spiro-OMeTAD;

[0028] The cathode is Ag.

[0029] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:

[0030] (1) The use of electron beam evaporation to prepare SiO2, Al2O3, MgO, and BeO thin films can accurately control the thickness of the film, and has the advantages of good film uniformity, fast speed, high efficiency, and strong scalability. The equipment is simple and the cost is lower, which is suitable for large-scale industrial preparation.

[0031] (2) Compared with the mesoporous insulating spacer layer, the insulating spacer layer of the present invention adopts a planar structure. This design simplifies the preparation process. By optimizing the interface contact between the electron transport layer and the perovskite layer, the planar structure barrier layer effectively reduces the interface recombination, further improving the photoelectric conversion efficiency of the solar cell.

[0032] (3) The insulating spacer layer prepared by electron beam evaporation technology has no adverse effect on the subsequent manufacturing process of perovskite solar cells and reduces production costs. The insulating spacer film is applied to perovskite solar cells to achieve effective passivation of interface defects, greatly reduce charge recombination losses, thereby reducing the recombination of electron and hole carriers, and thus improving the photoelectric conversion efficiency and long-term stability of the battery. The insulating spacer layer can not only block the erosion of the perovskite layer by external moisture and pollutants, reduce the direct contact between the perovskite layer and the electron transport layer, and extend the service life of the battery, but also inhibit internal ion migration and reduce performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the structure of a perovskite solar cell.

[0034] Figure 2 This is the forward scan JV curve of the perovskite solar cell.

[0035] Figure 3 This is the reverse scan JV curve of the perovskite solar cell.

[0036] Figure 4 Aging time diagram of perovskite solar cells. DETAILED DESCRIPTION

[0037] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0038] Example 1

[0039] This embodiment provides a method for preparing an insulating spacer layer by electron beam evaporation and application thereof.

[0040] In this embodiment, the prepared insulating spacer layer is applied to a perovskite solar cell. The structural schematic diagram of the perovskite solar cell is shown in FIG. Figure 1 As shown, the structure of the perovskite solar cell includes: a TiO2 electron transport layer, a SiO2 insulating spacer layer, a CsPbI 3-x Br xLight absorption layer, spiro-OMeTAD hole transport layer and cathode Ag.

[0041] 1. Cleaning of FTO anode substrate:

[0042] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol and anhydrous ethanol for 20 minutes in sequence, and then dried with nitrogen for later use.

[0043] 2. Preparation of TiO2 Electron Transport Layer

[0044] 99.99% high-purity TiO2 black sintered particles are selected as the evaporation source, and high-temperature tape is used to protect the bottom electrode area. The cleaned FTO glass is placed on the mask and placed in the coating machine. When the vacuum degree drops to 10 -4 Pa and the substrate temperature was raised to 200 ° C, the deposition process of TiO2 film was started, and the deposition rate was set to 0.5A / s. During the deposition process, the oxygen flow rate was maintained at 15sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 450 ° C for 2h to complete the preparation of the TiO2 electron transport layer.

[0045] 3. Preparation of SiO2 insulating spacer layer;

[0046] SiO2 particles were selected as the evaporation source, and high temperature tape was used to protect the bottom electrode area. The FTO glass containing the TiO2 electron transport layer was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 10 -4 Pa and the substrate temperature rises to 200 ° C, the deposition process of the SiO2 insulating spacer layer is started, and the deposition rate is set to 0.5A / s. During the deposition process, the oxygen flow rate is maintained at 15sccm until the entire deposition process is completed. After the evaporation process, the sample is placed in an oxygen-rich tube furnace and annealed at 450 ° C for 2 hours to complete the preparation of the SiO2 insulating spacer layer. The thickness of the prepared SiO2 insulating spacer layer is 5nm.

[0047] 4. CsPbI 3-x Br x Preparation of light absorbing layer:

[0048] HPIb3, PbBr2 and CsI were added into 1 mL of DMF and DMSO mixed solvent (the volume ratio of DMF and DMSO was 8.5:1.5) in the molar ratio of 3:2.85:0.15 to prepare 0.8 mol / L CsPbI 3-x Br xPerovskite solution. Place the CsPbI3-xBrx perovskite solution on a magnetic stirrer and stir at room temperature for 12 hours until the solution is completely dissolved to obtain CsPbI 3-x Br x Precursor solution for light absorbing layer. Spin coating CsPbI on FTO / TiO2 / SiO2 3-x Br x The precursor liquid of the light absorption layer was firstly spin-coated at 1000 rpm for 10 seconds, then at 3000 rpm for 30 seconds, and then the film was immediately placed on a heating platform for annealing at 200 °C for 5 minutes to obtain CsPbI 3-x Br x Light absorbing layer.

[0049] 5. Preparation of spiro-OMeTAD hole transport layer:

[0050] 72.3 mg spiro-OMeTAD, 29 uL TBP (tetra-tert-butylpyridine) and 18 uL Li-TFSI (lithium bis(trifluoromethanesulfonyl)imide) solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile) were added to 1 mL CB (chlorobenzene) to form a hole transport layer spiro-OMeTAD solution. 3-x Br x A layer of spiro-OMeTAD solution was spin-coated at a rotation speed of 7050 rpm for 30 s to obtain a spiro-OMeTAD hole transport layer.

[0051] 6. Preparation of cathode Ag:

[0052] A contact electrode Ag layer with a thickness of 70 nm was deposited on the spiro-OMeTAD hole transport layer using a thermal evaporation process. The evaporation rate was controlled at about 2 A / s to obtain a structure of FTO / TiO2 / SiO2 / CsPbI 3-x Br x / spiro-OMeTAD / Ag perovskite solar cell devices.

[0053] Example 2

[0054] This embodiment provides a method for preparing an insulating spacer layer by electron beam evaporation and application thereof.

[0055] In this embodiment, the prepared insulating spacer layer is applied to a perovskite solar cell. The structure of the perovskite solar cell includes: a TiO2 electron transport layer, an Al2O3 insulating spacer layer, a CsPbI 3-x Br xLight absorption layer, spiro-OMeTAD hole transport layer and cathode Ag.

[0056] 1. Cleaning of FTO anode substrate:

[0057] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol and anhydrous ethanol for 20 minutes in sequence, and then dried with nitrogen for later use.

[0058] 2. Preparation of TiO2 Electron Transport Layer

[0059] 99.99% high-purity TiO2 black sintered particles are selected as the evaporation source, and high-temperature tape is used to protect the bottom electrode area. The cleaned FTO glass is placed on the mask and placed in the coating machine. When the vacuum degree drops to 10 -4 Pa and the substrate temperature was raised to 200 ° C, the deposition process of TiO2 film was started, and the deposition rate was set to 0.1A / s. During the deposition process, the oxygen flow rate was maintained at 20sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 300 ° C for 3 hours to complete the preparation of the TiO2 electron transport layer.

[0060] 3. Preparation of Al2O3 insulating spacer layer;

[0061] Al2O3 particles were selected as the evaporation source, and high-temperature tape was used to protect the bottom electrode area. The FTO glass containing the TiO2 electron transport layer was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 10 -4 Pa and the substrate temperature was raised to 200 ° C, the deposition process of the Al2O3 insulating spacer was started, and the deposition rate was set to 0.1A / s. During the deposition process, the oxygen flow rate was maintained at 20sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 300 ° C for 3 hours to complete the preparation of the Al2O3 insulating spacer. The thickness of the prepared Al2O3 insulating spacer was 0.1nm.

[0062] 4. CsPbI 3-x Br x Preparation of light absorbing layer:

[0063] HPIb3, PbBr2 and CsI were added into 1 mL of DMF and DMSO mixed solvent (the volume ratio of DMF and DMSO was 8.5:1.5) in the molar ratio of 3:2.85:0.15 to prepare 0.8 mol / L CsPbI 3-x Br xPerovskite solution. Place the CsPbI3-xBrx perovskite solution on a magnetic stirrer and stir at room temperature for 12 hours until the solution is completely dissolved to obtain CsPbI 3-x Br x Precursor solution for light absorbing layer. Spin coating CsPbI on FTO / TiO2 / Al2O3 3-x Br x The precursor liquid of the light absorption layer was firstly spin-coated at 500 rpm for 10 seconds, then at 3000 rpm for 30 seconds, and then the film was immediately placed on a heating platform and annealed at 190 °C for 5 minutes to obtain CsPbI 3-x Br x Light absorbing layer.

[0064] 5. Preparation of spiro-OMeTAD hole transport layer:

[0065] 72.3 mg spiro-OMeTAD, 29 uL TBP and 18 uL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile) were added to 1 mL CB to form a hole transport layer spiro-OMeTAD solution. 3- x Br x A layer of spiro-OMeTAD solution was spin-coated at a rotation speed of 5000 rpm for 30 s to obtain a spiro-OMeTAD hole transport layer.

[0066] 6. Preparation of cathode Ag:

[0067] A contact electrode Ag layer with a thickness of 70 nm was deposited on the spiro-OMeTAD hole transport layer using a thermal evaporation process. The evaporation rate was controlled at about 1 A / s to obtain a structure of FTO / TiO2 / Al2O3 / CsPbI 3-x Br x / spiro-OMeTAD / Ag perovskite solar cell devices.

[0068] The key performance parameters of the perovskite solar cell prepared in this embodiment are: open circuit voltage of 1.041371V, short circuit current of 17.082655mA / cm 2 , the filling factor is 74.811120, the photoelectric conversion efficiency is increased to 13.308430, and in a 72-hour natural placement test, the perovskite solar cell with the introduction of the Al2O3 insulating spacer layer still maintains 95% of the original efficiency.

[0069] Example 3

[0070] This embodiment provides a method for preparing an insulating spacer layer by electron beam evaporation and application thereof.

[0071] In this embodiment, the prepared insulating spacer layer is applied to a perovskite solar cell. The structure of the perovskite solar cell includes: a TiO2 electron transport layer, a MgO insulating spacer layer, a CsPbI 3-x Br x Light absorption layer, spiro-OMeTAD hole transport layer and cathode Ag.

[0072] 1. Cleaning of FTO anode substrate:

[0073] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol and anhydrous ethanol for 20 minutes in sequence, and then dried with nitrogen for later use.

[0074] 2. Preparation of TiO2 Electron Transport Layer

[0075] 99.99% high-purity TiO2 black sintered particles were selected as the evaporation source, and high-temperature tape was used to protect the bottom electrode area. The cleaned FTO glass was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 1×10 -5 Pa and the substrate temperature was raised to 100 ° C, the deposition process of TiO2 film was started, and the deposition rate was set to 1A / s. During the deposition process, the oxygen flow rate was maintained at 5sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 600 ° C for 1 hour to complete the preparation of the TiO2 electron transport layer.

[0076] 3. Preparation of MgO insulating spacer layer;

[0077] MgO particles were selected as the evaporation source, and high-temperature tape was used to protect the bottom electrode area. The FTO glass containing the TiO2 electron transport layer was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 1×10 -5 Pa and the substrate temperature was raised to 100 ° C, the deposition process of the MgO insulating spacer was started, and the deposition rate was set to 1A / s. During the deposition process, the oxygen flow rate was maintained at 5sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 600 ° C for 1 hour to complete the preparation of the MgO insulating spacer. The thickness of the prepared MgO insulating spacer was 500nm.

[0078] 4. CsPbI 3-x Br x Preparation of light absorbing layer:

[0079] HPIb3, PbBr2 and CsI were added into 1 mL of DMF and DMSO mixed solvent (the volume ratio of DMF and DMSO was 8.5:1.5) in the molar ratio of 3:2.85:0.15 to prepare 0.8 mol / L CsPbI 3-x Br x Perovskite solution. Place the CsPbI3-xBrx perovskite solution on a magnetic stirrer and stir at room temperature for 12 hours until the solution is completely dissolved to obtain CsPbI 3-x Br x Precursor solution for light absorbing layer. Spin coating CsPbI on FTO / TiO2 / MgO 3-x Br x The precursor liquid of the light absorption layer was firstly spin-coated at 1500 rpm for 10 s, then at 6000 rpm for 30 s, and then the film was immediately placed on a heating platform and annealed at 210 °C for 5 min to obtain CsPbI 3-x Br x Light absorbing layer.

[0080] 5. Preparation of spiro-OMeTAD hole transport layer:

[0081] 72.3 mg spiro-OMeTAD, 29 uL TBP (tetra-tert-butylpyridine) and 18 uL Li-TFSI (lithium bis(trifluoromethanesulfonyl)imide) solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile) were added to 1 mL CB (chlorobenzene) to form a hole transport layer spiro-OMeTAD solution. 3-x Br x A layer of spiro-OMeTAD solution was spin-coated at a rotation speed of 7000 rpm for 30 s to obtain a spiro-OMeTAD hole transport layer.

[0082] 6. Preparation of cathode Ag:

[0083] A contact electrode Ag layer with a thickness of 70 nm was deposited on the spiro-OMeTAD hole transport layer using a thermal evaporation process. The evaporation rate was controlled at about 3 A / s to obtain a structure of FTO / TiO2 / MgO / CsPbI 3-x Br x / spiro-OMeTAD / Ag perovskite solar cell devices.

[0084] The key performance parameters of the perovskite solar cell prepared in this embodiment are: open circuit voltage of 1.010710V, short circuit current of 17.057470mA / cm 2, the filling factor is 72.296203, the photoelectric conversion efficiency is increased to 12.463972, and in a 72-hour natural placement test, the perovskite solar cell with the introduction of the MgO insulating spacer layer still maintains 90% of the original efficiency.

[0085] Example 4

[0086] This embodiment provides a method for preparing an insulating spacer layer by electron beam evaporation and application thereof.

[0087] In this embodiment, the prepared insulating spacer layer is applied to a perovskite solar cell. The structure of the perovskite solar cell includes: a TiO2 electron transport layer, a BeO insulating spacer layer, a CsPbI 3-x Br x Light absorption layer, spiro-OMeTAD hole transport layer and cathode Ag.

[0088] 1. Cleaning of FTO anode substrate:

[0089] The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol and anhydrous ethanol for 20 minutes in sequence, and then dried with nitrogen for later use.

[0090] 2. Preparation of TiO2 Electron Transport Layer

[0091] 99.99% high-purity TiO2 black sintered particles were selected as the evaporation source, and high-temperature tape was used to protect the bottom electrode area. The cleaned FTO glass was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 5×10 -3 Pa and the substrate temperature was raised to 350 ° C, the deposition process of TiO2 film was started, and the deposition rate was set to 1A / s. During the deposition process, the oxygen flow rate was maintained at 5sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 800 ° C for 2h to complete the preparation of the TiO2 electron transport layer.

[0092] 3. Preparation of BeO insulating spacer layer;

[0093] BeO particles were selected as the evaporation source, and high-temperature tape was used to protect the bottom electrode area. The FTO glass containing the TiO2 electron transport layer was placed on the mask and placed in the coating machine. When the vacuum degree dropped to 5×10 -3Pa and the substrate temperature was raised to 350 ° C, the deposition process of the BeO insulating spacer was started, and the deposition rate was set to 1 A / s. During the deposition process, the oxygen flow rate was maintained at 10 sccm until the entire deposition process was completed. After the evaporation process, the sample was placed in an oxygen-rich tube furnace and annealed at 800 ° C for 2 hours to complete the preparation of the BeO insulating spacer. The thickness of the prepared BeO insulating spacer was 1 μm.

[0094] 4. CsPbI 3-x Br x Preparation of light absorbing layer:

[0095] HPIb3, PbBr2 and CsI were added into 1 mL of DMF and DMSO mixed solvent (the volume ratio of DMF and DMSO was 8.5:1.5) in the molar ratio of 3:2.85:0.15 to prepare 0.8 mol / L CsPbI 3-x Br x Perovskite solution. Place the CsPbI3-xBrx perovskite solution on a magnetic stirrer and stir at room temperature for 12 hours until the solution is completely dissolved to obtain CsPbI 3-x Br x Precursor solution for light absorbing layer. Spin coating CsPbI on FTO / TiO2 / BeO 3-x Br x The precursor liquid of the light absorption layer was firstly spin-coated at 1500 rpm for 10 s, then at 6000 rpm for 30 s, and then the film was immediately placed on a heating platform and annealed at 210 °C for 5 min to obtain CsPbI 3-x Br x Light absorbing layer.

[0096] 5. Preparation of spiro-OMeTAD hole transport layer:

[0097] 72.3 mg spiro-OMeTAD, 29 uL TBP and 18 uL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile) were added to 1 mL CB to form a hole transport layer spiro-OMeTAD solution. 3- x Br x A layer of spiro-OMeTAD solution was spin-coated at a rotation speed of 7000 rpm for 30 s to obtain a spiro-OMeTAD hole transport layer.

[0098] 6. Preparation of cathode Ag:

[0099] A contact electrode Ag layer with a thickness of 70 nm was deposited on the spiro-OMeTAD hole transport layer using a thermal evaporation process. The evaporation rate was controlled at about 3 A / s to obtain a structure of FTO / TiO2 / BeO / CsPbI 3-x Br x / spiro-OMeTAD / Ag perovskite solar cell devices.

[0100] The key performance parameters of the perovskite solar cell prepared in this embodiment are: open circuit voltage of 0.973443V, short circuit current of 16.905000mA / cm 2 , the filling factor is 66.999552, the photoelectric conversion efficiency is increased to 11.025483, and in a 72-hour natural placement test, the perovskite solar cell with the introduction of the BeO insulating spacer layer still maintains 90% of the original efficiency.

[0101] Example 5

[0102] This example provides the performance characterization results of perovskite solar cells.

[0103] This example is the performance characterization result of a solar cell with the introduction of a SiO2 insulating spacer layer (same as Example 1), which significantly optimizes the performance of the perovskite solar cell. Figure 2 and Figure 3 The JV (current density-voltage) characteristic curves of the improved perovskite solar cell under forward scanning and reverse scanning conditions are shown respectively. Figure 2 and Figure 3 The key performance parameters of the perovskite solar cell prepared by the present invention are obtained by analysis: the open circuit voltage is 0.933693V, the short circuit current is 17.885756mA / cm 2 , the filling factor is 69.504906%, and the photoelectric conversion efficiency is increased to 11.607183%. Figure 4 The aging time of the improved perovskite solar cell of the present invention is as follows. In a 72-hour natural placement test, the perovskite solar cell with the SiO2 insulating spacer layer maintained more than 90% of the original efficiency, while the efficiency of the perovskite solar cell without the SiO2 insulating spacer layer dropped to 60% of the original efficiency. The above experimental results show that the improved perovskite solar cell of the present invention can maintain stable performance in long-term operation.

[0104] The SiO2 insulating spacer effectively reduces the interface recombination between the perovskite layer and the electron transport layer, reduces energy loss, improves charge extraction efficiency, and provides an excellent barrier to prevent moisture and environmental factors from corroding the perovskite layer, thereby extending the battery life. This makes solar cells more durable in practical applications, and reduces the impact on the environment by using environmentally friendly materials and simplifying production processes, meeting the requirements of sustainable development.

[0105] The electron beam evaporation method used in the present invention shows extremely high process stability and repeatability in the process of preparing the SiO2 insulating spacer layer, significantly reducing the reliance on repetitive labor in the traditional production process. The introduction of this method means that production personnel no longer need to frequently adjust process parameters or perform cumbersome interlayer processing, thereby reducing the complexity and labor intensity of manual operations. The electron beam evaporation method has a high degree of automation and can achieve continuous and uniform thin film deposition, ensuring consistency and reliability in large-scale production processes.

[0106] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.

Claims

1. A method for improving the efficiency of a perovskite solar cell, characterized in that: Introducing an insulating spacer layer between the electron transport layer and the perovskite layer of a perovskite solar cell; The thickness of the insulating spacer layer is 0.1 nm to 1 μm.

2. The method according to claim 1, characterized in that The insulating spacer layer is SiO2, Al2O3, MgO, BeO; The insulating spacer layer is prepared by electron beam evaporation.

3. A method for preparing a perovskite solar cell, characterized in that: include: An electron transport layer and an insulating spacer layer are deposited and annealed on an anode substrate by electron beam evaporation; a perovskite layer and a hole transport layer are prepared by solution spin coating, and the perovskite layer is annealed; The cathode was prepared by thermal evaporation.

4. The preparation method according to claim 3, characterized in that: The FTO conductive glass of the anode substrate is cleaned with deionized water, acetone, isopropyl ketone and anhydrous ethanol ultrasonically in sequence, and then blown dry with nitrogen.

5. The preparation method according to claim 3, characterized in that: The parameters of the electron beam evaporation method are set as follows: the vacuum degree is 1×10 -5 ~5×10 -3 Pa, temperature is 100-350°C, deposition rate is 0.1-1A / s, oxygen flow rate is 5-20sccm; The conditions for annealing the electron transport layer and the insulating spacer layer are: annealing temperature is 300-800° C., and annealing time is 1-3 hours.

6. The preparation method according to claim 3, characterized in that: The spin coating process of the perovskite layer is 500-1500 rpm for 10 seconds, and then 3000-6000 rpm for 30 seconds; The conditions for annealing the perovskite layer are: annealing temperature is 190-210° C., and annealing time is 5-15 min; The spin coating process of the hole transport layer is 5000-7000 rpm for 30 seconds.

7. The preparation method according to claim 3, characterized in that: The rate of the thermal evaporation method is 1 to 3 A / s.

8. The perovskite solar cell prepared by the preparation method according to any one of claims 3 to 7.

9. The perovskite solar cell according to claim 8, characterized in that: The perovskite solar cell comprises an electron transport layer, an insulating spacer layer, a perovskite layer, a hole transport layer and a cathode which are sequentially arranged on an anode substrate.

10. The perovskite solar cell according to claim 9, characterized in that: The anode substrate is FTO conductive glass; The electron transport layer is TiO2; The perovskite layer is CsPbI 3-x Br x ; The hole transport layer is spiro-OMeTAD; The cathode is Ag.

Citation Information

Patent Citations

  • Efficient perovskite solar cell and preparation method thereof

    CN105428438A

  • Perovskite solar cell and preparation method thereof

    CN118870841A

  • Perovskite-based solar cell

    KR1020170002967A

Cited By

  • Perovskite battery based on composite interface modification engineering and preparation method thereof

    CN121419459A

  • Perovskite solar cell based on composite interface modification engineering and preparation method thereof

    CN121419459B